2017
DOI: 10.1017/s1041610217000254
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate inaccuracy in predicting older adults’ desire for life-sustaining interventions in the event of decisional incapacity: is it due in part to erroneous quality-of-life assessments?

Abstract: ISRCTN89993391.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
4
10
0
Order By: Relevance
“…undertreat (e.g., Bravo et al, 2017). The current findings are more consistent with literature regarding discrepancies in estimating levels of pain or discomfort experienced by others.…”
Section: Surrogates' Accuracy On Decision Vignettessupporting
confidence: 89%
See 2 more Smart Citations
“…undertreat (e.g., Bravo et al, 2017). The current findings are more consistent with literature regarding discrepancies in estimating levels of pain or discomfort experienced by others.…”
Section: Surrogates' Accuracy On Decision Vignettessupporting
confidence: 89%
“…This finding adds to the body of evidence suggesting that individuals who make decisions for patients in end-of-life situations may not be trusted to consistently select the treatment that the patient would have wanted (Torke, 2008). The level of agreement found in the current study is notably lower than that reported in a systematic review of the literature by Shalowitz et al (2006; 68% agreement, on average), yet it is consistent with levels reported by more recent investigations of surrogate decision-making accuracy (e.g., Bravo et al, 2017).…”
Section: Surrogates' Accuracy On Decision Vignettessupporting
confidence: 85%
See 1 more Smart Citation
“…11 Differences in QOL ratings were associated with surrogates' inaccuracy of predicting older adults' treatment preferences in hypothetical situations. 12 For individuals with dementia, discrepancy was observed between selfrated and carer-rated perceptions of QOL. 13,14 A review of dementia specific-measurement scales found a lack of consensus on measures of QOL.…”
Section: Substitutementioning
confidence: 99%
“…Substitute decision‐making by healthcare proxies provides a view to help direct medical management, but an opinion of QOL by a surrogate does not necessarily concur with the QOL ratings of the person they represent . Differences in QOL ratings were associated with surrogates’ inaccuracy of predicting older adults’ treatment preferences in hypothetical situations …”
mentioning
confidence: 99%